New species of the Rhaconotusjacobsoni group (Hymenoptera, Braconidae, Doryctinae) from Vietnam - Oanh, Nguyen Thi (Zookeys, 2019)
Abstract. Four new species of the genus Rhaconotus Ruthe from Vietnam are described and illustrated – Rhaconotusdirectus Long, sp. nov., R.laevigatus Long, sp. nov., R.robustus Long, sp. nov., and R.simulatus Long, sp. nov. A key to species of Rhaconotusjacobsoni group from the Oriental region is provided.